Riding the merger wave: the gatekeeping role of auditors - Carnes, Robert (Review of Accounting Studies, 2025)
I investigate whether auditors engage in greater monitoring of acquirers during industry merger waves. Merger waves are periods of industry transformation (i.e., disruption) that are accompanied by greater uncertainty, limited internal and external corporate monitoring, and poorer acquisition performance. These factors threaten the quality of acquirers’ financial reports. I test whether auditors respond to these periods by increasing their effort, which improves audit quality, and by resigning from high-risk engagements to reduce their portfolio risk. For in-wave audits, I find that audit fees are higher, financial statements are less likely to be materially misstated, auditors are more likely to timely identify and report internal control deficiencies, and auditor resignations are higher. Overall, these findings are consistent with auditors adapting to merger waves and providing higher-quality corporate monitoring within the scope of their influence. Importantly, this study provides insights that broaden our understanding of auditing and M&A transactions.